Steam-induced changes in surface characteristics and corrosion resistance of spark-anodized titanium - Chen, Zhaoxiang (2015)
Titanium was spark-anodized in 1 M phosphoric acid solution. Surface characteristics and corrosion resistance of spark-anodized titanium were investigated before and after the steam exposure at 180 °C. It was found that spark-anodizing of titanium produced a layer of poorly crystallized TiO2 film with the incorporation of phosphate anions. The oxide film exhibited a porous microstructure with many craters and micro-projections on the surface. After the steam exposure for 48 h, the crystallinity of anodic TiO2 increased greatly. The original dense and smooth micro-projection surface became very loose and rough, and fine Ti(OH)PO4 crystals formed and congregated there. A phase transition mechanism has been proposed based on the experimental observations. The corrosion behavior investigation has shown that the steam exposure could reduce the corrosion resistance of spark-anodized titanium greatly.